Penerapan Metode Diskusi pada Mata Pelajaran PAI sebagai Upaya Meningkatkan Aktivitas Belajar Siswa Kelas VII di SMP Negeri 2 Mayang - Tadika Hazelina Putri; Bahar Agus Setiawan; Siti Nursyamsiyah (Yayasan Madinah Al-Aziziyah, 2026)
The application of a learning method is very much needed by students, especially in Islamic Religious Education subjects which are often considered boring due to the lack of student involvement, therefore, a discussion method is needed that can create an active and effective learning atmosphere. The purpose of this study is to describe the application of the discussion method in Islamic Religious Education subjects in improving the learning activities of 7th grade students of SMP Negeri 2 Mayang. The research approach uses a qualitative with a descriptive research type, in this study the Islamic Religious Education teacher and 7th grade students became the research subjects. Data were obtained through interviews, observations, and documentation. The data obtained were then analyzed with the stages of data reduction and presentation, then conclusions were drawn so that an overview of the application of the discussion method in improving student learning activities was obtained. The application of the discussion method was carried out in several stages, namely, interactive lectures and interviews, where both stages can involve students in the learning process, train them to interact and communicate well. The existence of this method can improve student learning activities in understanding the material, daring to express opinions, express ideas, think critically and not passively. Student learning activities can increase because the teacher uses a discussion method that makes students involved in the learning process. Thus, the increase in student learning activities is closely related to learning methods, especially discussion methods that contribute to the learning process.